1996
DOI: 10.1029/96gl00415
|View full text |Cite
|
Sign up to set email alerts
|

Kilometric irregularities in the E and F regions of the daytime equatorial ionosphere observed by a high resolution HF radar

Abstract: During the International Equatorial Electrojet Year, high resolution vertical HF coherent radar experiments were performed in the Ivory Coast (9°24′62″N, 5°37′38″W) at frequencies in the range 1–8 MHz. Kilometric scale irregularities were observed in the E and F regions of the daytime equatorial ionosphere. These irregularities constitute a large sporadic E layer within the altitude range 100 to 150 km, larger than the width of the equatorial electrojet. The higher part of this irregular region is detached in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 14 publications
4
33
0
Order By: Relevance
“…They produce also an increase of the echo width of 40 km at 250 km to 15 km at 440 km corresponding to 10±12 km at 180±300 km after ionogram inversion. The period of observation of these irregularities is correlated with that of the irregularities in the electrojet region (Blanc et al, 1996). Similar amplitude¯uctuations are never observed in the evening, when the E-region irregularities disappear or in the morning before they appear.…”
Section: Observationssupporting
confidence: 51%
See 2 more Smart Citations
“…They produce also an increase of the echo width of 40 km at 250 km to 15 km at 440 km corresponding to 10±12 km at 180±300 km after ionogram inversion. The period of observation of these irregularities is correlated with that of the irregularities in the electrojet region (Blanc et al, 1996). Similar amplitude¯uctuations are never observed in the evening, when the E-region irregularities disappear or in the morning before they appear.…”
Section: Observationssupporting
confidence: 51%
“…Echolocation measurements showed that echoes on these irregularities arise both from vertical and oblique re¯ections in the east-west direction. The use of several radar frequencies allowed to locate them close to the re¯ection level as the Doppler frequency shift was proportional to the radar frequency (Blanc et al, 1996). These irregularities are di cult to observe on the ionograms as they just appear as an increase in the echo width of few tens of kilometers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An HF Radar was operated by the CEA (Commisariat aÁ l'Energie Atomique) during three months in 1993 and three other months in 1994 at Korhogo (Blanc et al, 1996). It allowed the study of the E-and F-layer density pro®les in the ionosphere, virtual re¯ection heights, echo power spectra, and consequently Doppler shifts, diurnal drift, plasma instabilities, and irregular structures (spread F, plume, small-scale inhomogeneities) by echo location.…”
Section: The 1992 Ieey Experimentsmentioning
confidence: 99%
“…The QP echoes were reported from many radars locations (Yamamoto et al, , 1992Woodman et al, 1991;Tsunoda et al, 1994Tsunoda et al, , 1995, which were reported to be usually located in the valley region between the E-and F-regions and extend from 177 km to 215 km (Tsunoda et al, 1995) and the slope of the range rate was about −100 m/s and always negative. The QP echoes first reported by Balsley (1964) as 150 km echoes were studied close to the magnetic equator in great detail (Royrvik and Miller, 1981;Royrvik, 1982;Kudeki and Fawcett, 1993;Hysell et al, 1997;Chau and Woodman, 2004;Chau, 2004;Kudeki et al, 1998;Euklund, 2000, 2004;Blank et al, 1996;de Paula and Hysell, 2004). There were reports from the Indian MST radar at Gadanki outside the equatorial electrojet (Geomag.…”
Section: Introductionmentioning
confidence: 99%